(untitled) (Bangladesh Journal of Bioethics, 2019)
ABC20 will be held at Dhaka, Bangladesh, in cooperation with Social Science Research Council, Bangladesh, Planning Division, Ministry of Planning; Directorate General of Health Services (DGHS), Ministry of Health & Family Welfare; Bangladesh Medical Research Council (BMRC); Asian Bioethics Association (ABA) and Eubios Ethics Institute, Thailand, New Zeeland and Japan. It provides opportunity for all scholars around the world to gather feedback on their research, maximize networking opportunities, and learn the latest information and methodologies on bioethics. The previous conferences held in China, Japan, Korea, Turkey, Thailand, Malaysia, Indonesia, India, Iran, the Philippines and Taiwan. The conference will bring together scholars and policy makers from many disciplines all around the world (beyond the Asia and the Pacific) to discuss and deliberate the latest ethical issues in biomedicine, biotechnology, science, social science and education on the dilammas facing today for humanity.